Desempenho de unidades gotejadoras operando com diluições de efluentes de laticínios e de água de abastecimento público em escala laboratorial - Marques, Blake Charles Diniz (Universidade Federal Rural do Semi-Árido, 2016)
The problem of water crisis is directly related to factors such as increasing population, increased demand for water, climate variations and deterioration of existing resources. In the semi-arid Northeast the predominant characteristics of reduced rainfall, high temperature and high evaporative rate, make the shortage of water for long periods of the year, more and more recurrent. Liquid effluents of dairy industries have the potential for agricultural use due to nutrient intake. However, this practice involves technical feasibility issues inherent in the method of irrigation adopted where the clogging of the emitters becomes more vulnerable, but can be attenuated with the technique of dilution in water. Given the above, the study aimed to analyze the hydraulic performance drippers units applying wastewater dilution dairy (ARL) and the public water supply (AA). For this, it was set up a trial bench, the Pollution Laboratory and Land Degradation (LPDS) of the Federal Rural University of Semi-Arid (UFERSA) campus Mossoro-RN, consisting of four drippers units operating with four different dilutions of ARL in AA (1A0E; 1A1E; 2A1E and 3A1E) and five types of drippers (G1, G2, G3, G4 and G5). The hydraulic performance of drippers units was obtained every 40 hours of operation with dilutions of ARL AA for 200 h at 2014 20/10 10/04 2015 period, using the indicators drip flow ( Q) flow variation coefficient (CVQ), statistical uniformity coefficient (US), distribution uniformity coefficient (CUD) and reduction of the relative flow rate (Dr). At the same time, they quantified the physicochemical and microbiological attributes of ARL dilutions AA. Data were submitted to analysis of simple and multiple regression and parametric test of Pearson correlations. Among the physicochemical and microbiological characteristics of dairy effluent, solid values suspended (SS), dissolved solids (DS), pH and total iron (Fe) represented drippers clogging risk ranging from moderate to high. The SS features, SD, pH and Fe predominated in multiple linear regression equations adjusted to the hydraulic performance variables, combinations between types of drippers and dairy effluent dilution levels in the public water supply. At the end of the experimental tests, samples of emitters biofouling were subjected to photographic records and analyzes by optical microscopy and scanning electron microscopy (SEM), showing the formation of a biofilm on the entire internal area of the sampled emitters resulting in partial clogging and total tested drippers, thus affecting the hydraulic system performance. Hydraulic performance indicators Q, CUD, CVQ and Us satisfactorily expressed the drippers obstruction levels, while Dr. underestimated the risks of obstruction brought about by dairy effluent. The greater susceptibility to clogging occurred in the dripper G2 operating in 1A1E and 3A1E dilutions. On the other hand, the dripper G5 was less susceptible to clogging at operating 2A1E dilution. The screen filter provided good removal of SS with the same size or greater than 130 μm
Keywords: Reuso; Efluente lácteo; Emissores; Irrigação localizada; Dairy effluent reuse; Emitters; Irrigation; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO